2022
DOI: 10.1002/agm2.12194
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of potentially inappropriate medications use in Indian elderly population and their impact on quality of life using Beers criteria

Abstract: Background Polypharmacy is principal cause of potentially inappropriate medications (PIMs) in elderly patients, which include over prescribing, under prescribing, and misprescribing. Methods Elderly subjects (≥60 years), of either sex, receiving two or more medications for one or more chronic ailments, attending Geriatrics Outpatient Department (OPD), at All India Institute of Medical Sciences (AIIMS) New Delhi, were included. Their prescriptions were assessed for PIMs by using Beers criteria 2015 and were fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Following exclusion of 213 duplicate studies, 1258 studies were excluded by the titles and abstracts. Ninety-four studies with 371 224 692 older outpatients were included for analysis (Figure 1; eAppendix 2 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following exclusion of 213 duplicate studies, 1258 studies were excluded by the titles and abstracts. Ninety-four studies with 371 224 692 older outpatients were included for analysis (Figure 1; eAppendix 2 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-one studies were conducted in Asia, followed by 22 studies in Europe, 14 studies in North America, 8 studies in South America, 7 studies in Africa, and 2 studies in Oceania. Between 1999 and 2021, a total of 51 studies were performed in high-income countries, 23 studies in upper- to middle-income countries, 17 studies in lower- to middle-income countries, and 3 studies in low-income countries. Sixty-three studies of the PIM prevalence estimates were based on the Beers criteria, 26 studies…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study included 380 patients with an average age of 65.4 years, and 65% of the prescriptions included one or more PIMs. 21 Pattani et al 22 reported similar results; 200 hospitalized older adults had a PIM use prevalence of 53%.…”
Section: Discussionmentioning
confidence: 82%